Chaplains' Engagement with Suicidality among Their Service Users: Findings from the VA/DoD Integrated Mental Health Strategy. Issue 2 (10th August 2015) - Kopacz, Marek S.; Nieuwsma, Jason A.; Jackson, George L.; Rhodes, Jeffrey E.; Cantrell, William C.; Bates, Mark J.; Meador, Keith G.
Abstract : Chaplains play an important role in supporting the mental health of current and former military personnel; in this study, the engagement of Department of Veterans Affairs (VA), Army, Navy, and Air Force chaplains with suicidality among their service users were examined. An online survey was used to collect data from 440 VA and 1, 723 Department of Defense (DoD) chaplains as part of the VA/DoD Integrated Mental Health Strategy. Differences were noted for demographics, work setting characteristics, encountering suicidality, and self‐perceived preparation for dealing with suicidality. Compared to DoD chaplains, VA chaplains encounter more at‐risk service users, yet feel less prepared for dealing with suicidality.